Analysis Of Feasibility Study For Waste Processing Business (Case Study on the Unit Pengolahan Sampah Sejahtera of BUMDes Tirto) - Rizky Ardianto; Hendrik Suhendri; Sri Andika Putri; Agnes Quartina Pudjiastuti (International Journal of Management and Business, 2025)
This study aims to analyze the business feasibility of waste processing units run by Tirto Village-Owned Enterprises (BUMDes) in Landungsari Village, Malang Regency. The background of this study is the increase in waste generation due to community activities and the weak village-based waste management system. The analysis methods used in the financial aspect include Net Present Value (NPV), Internal Rate of Return (IRR), and Payback Period (PP). The results of the study show that the waste processing business run by BUMDes Tirto is feasible from various aspects. Legally, this unit is in accordance with the provisions of Law No. 6 of 2014 concerning Villages. From the market side, there is a potential consumer from households and boarding houses that continues to increase every year. Technically and operationally, this business already has a simple but functional waste collection and sorting facility. In the financial aspect, the NPV value obtained was IDR 34,291,122, IRR was 28%, and PP for 2 years and 7.4 months, all of which showed that this business was financially viable. Therefore, this business unit is considered to have good development prospects, both in terms of economic, social, and environmental sustainability. It is advisable for BUMDes to start designing strategic steps to improve the effectiveness of waste management, including adding supporting facilities and equipment, as well as encouraging broader community involvement, so that the benefits of the activities can be felt more significantly